2017
DOI: 10.1080/10408398.2016.1243088
|View full text |Cite
|
Sign up to set email alerts
|

Mucus and microbiota as emerging players in gut nanotoxicology: The example of dietary silver and titanium dioxide nanoparticles

Abstract: Given the growing use of nanotechnology in many common consumer products, including foods, evaluation of the consequences of chronic exposure to nanoparticles in humans has become a major public health issue. The oral route of exposure has been poorly explored, despite the presence of a fraction of nanosized particles in certain food additives/supplements and the incorporation of such particles into packaging in contact with foods. After their ingestion, these nanoparticles pass through the digestive tract, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 84 publications
0
51
0
Order By: Relevance
“…Currently, citrate, d ‐glucose, sodium dodecyl sulfate, polyvinylpyrrolidone (PVP), polyethylene glycol, amines, polysaccharides (including chitosan) and leaf extracts have been used as stabilizers in the manufacture of AgNPs (Krishnaraj et al, ; Sharma, Yngard, & Lin, ). Stabilizers are used to control the process of AgNP generation and thereafter prevent their aggregation (Liu, Cao, Tang, Chen, & Wang, ; Mercier‐Bonin, Despax, Raynaud, Houdeau, & Thomas, ). Both aggregation and surface coatings can change AgNP toxicity (Lu et al, ) by not only slowing down biodegradation but also significantly increasing antibacterial activity (Wang, Zhao, Zhu, Fang, & Ren, ).…”
Section: Structure‐activity Relationships Of Silver Nanoparticles Witmentioning
confidence: 99%
See 3 more Smart Citations
“…Currently, citrate, d ‐glucose, sodium dodecyl sulfate, polyvinylpyrrolidone (PVP), polyethylene glycol, amines, polysaccharides (including chitosan) and leaf extracts have been used as stabilizers in the manufacture of AgNPs (Krishnaraj et al, ; Sharma, Yngard, & Lin, ). Stabilizers are used to control the process of AgNP generation and thereafter prevent their aggregation (Liu, Cao, Tang, Chen, & Wang, ; Mercier‐Bonin, Despax, Raynaud, Houdeau, & Thomas, ). Both aggregation and surface coatings can change AgNP toxicity (Lu et al, ) by not only slowing down biodegradation but also significantly increasing antibacterial activity (Wang, Zhao, Zhu, Fang, & Ren, ).…”
Section: Structure‐activity Relationships Of Silver Nanoparticles Witmentioning
confidence: 99%
“…(Albanese et al, ; Lesniak et al, ; Treuel et al, ; Walkey, Olsen, Guo, Emili, & Chan, ). Additionally, mucus plays an essential role in the preservation of intestinal homeostasis (Mercier‐Bonin et al, ), and Georgantzopoulou et al () found that intestinal mucus affects the transmission rate of different AgNPs. AgNP exclusion due to mucus, which results in the immobilization of larger‐sized particles, decreases their interaction with the cell membrane and consequently reduces their toxicity.…”
Section: Potential Transformation and Degradation Of Ingested Silver mentioning
confidence: 99%
See 2 more Smart Citations
“…Ag NPs and Ti 2 O NPs caused changes in the microbiota and mucus in intestine (Mercier-Bonin et al, 2016). Taylor et al (2015) used an in vitro colon model found that ZnO NPs caused significant changes to the microbial community’s phenotype, which might be related to overall health effects.…”
Section: Introductionmentioning
confidence: 99%